0930 A single 7T MRI brain scan accurately predicts eventual diagnosis of MS in cases with initial diagnostic uncertainty. Issue 3 (9th February 2012) - Mistry, N; Dixon, J; Tallantyre, E; Jaspan, T; Morgan, P; Morris, P; Evangelou, N
Abstract : Background: In vivo T2*-weighted 7 Tesla (7T) MRI can be used to visualise central veins in most MS lesions (Tallantyre et al 2008). The percentage of lesions with a visible central vein reliably distinguishes patients known to have MS from patients with microangiopathic white matter brain lesions (Tallantyre et al 2011). Objective: To prospectively assess the predictive value of a single T2*-weighted 7T MRI scan, for patients that a Neurologist and Neuroradiologist could not diagnose without further paraclinical testing and follow-up. Patients and methods: Currently 20 patients have been recruited. They were undiagnosed despite assessment by a consultant Neurologist and interpretation of conventional hospital MRI scanning by a consultant Neuroradiologist. Image acquisition and analysis (blinded to clinical data) was performed using methods previously described (Tallantyre et al 2011). Results: Of the 20 patients studied, 18 have a diagnosis from their Neurologist. All 13 patients with an eventual diagnosis of demyelinating disease had central veins visible in >40% of brain lesions. All five patients with an eventual non-MS diagnosis had central veins visible in <40% of lesions. No patient with positive CSF oligoclonal bands had <40% of lesions with central veins. Conclusion: In the current cohort T2*-weighted 7T MRI had 100% positive and negative predictive value for MS. Translation of this technique to clinically available 3T MRI scanners could overhaul future diagnostic algorithms.